Analisis Karakteristik Ibu Hamil Dengan HBsAg Positif Yang Berhubungan Dengan Kejadian Hepatitis B Dalam Kehamilan Di RSUD dr. H. Koesnadi Bondowoso.: analisis karakteristik demografi ibu hamil dengan HBsAg Positif di RSUD dr. H. Koesnadi Bondowoso - Siwi, Yunita Anindito Purwo Erdi; Prijatni, Ida; Sutrisno, Sutrisno (Poltekkes Kemenkes Malang & IBI Ranting Pendidikan Kota Malang, 2020)
Hepatitis B is an infectious disease that is a major health problem in the world, including in Indonesia. This disease can attack pregnant women and can affect the fetus they are carrying. This study aims to identify the chance of hepatitis B incidence based on the characteristics of pregnant women with HBsAg positive at dr. H. Koesnadi Bonsowoso. This research is a descriptive quantitative analytic study, with a population of HBsAg Positive pregnant women in 2019 with a sample size of 76 mothers who were taken using a total sampling technique. Collecting data using secondary data from the medical records of dr. H Koesnadi Bondowoso. The results showed that the characteristics of pregnant women with positive HBsAg had the highest chance in the age group 20-34 years (82.9%), mothers who do not work (75%), husbands who work as private employees (40.8%), mothers who do not have a history of surgery (82.9%), and in multigravidas (64.5%), it is concluded that mothers aged 20-34 years, do not work, have no history of surgery, are multigravida, and have husbands who work as private employees have a high chance of getting Hepatitis B in pregnancy. Screening efforts for pregnant women are needed to reduce the risk of transmission from mother to fetus. Pre-pregnancy screening efforts also need to be done on husband and wife to reduce the risk of transmission between partners. Keywords: Hepatitis B, HBsAg, Characteristics of Pregnant Women